Intracranial Pressure and Vascular Aging: A Narrative Review on its Role in Monitoring Cognitive Decline - Mikaelle Costa Correia; Matheus Henrique de Jesus Lima; Amanda Rodrigues Bitencourt; Aline Rosa de Castro Carneiro; Rogério Orlow de Oliveira; Sayuri Inuzuka; Adriana Camargo Oliveira; Marco Túlio Araújo Pedatella; Polyana Vulcano de Toledo Piza; Gustavo Frigieri; Weimar Kunz Sebba Barroso (Artery Research)
Abstract Vascular aging is closely associated with the development of cardiovascular disease and cognitive impairment and is a determining factor in overall morbidity and mortality. The continued presence of modifiable risk factors, such as hypertension, diabetes mellitus, obesity, and a sedentary lifestyle, accelerates this process and contributes to its complications. In this context, arteriosclerosis and atherosclerosis play a central role in the loss of arterial elasticity, increasing susceptibility to cardiovascular and cerebrovascular events. Arterial stiffness, measured by pulse wave velocity, has been correlated with the risk of dementia and cognitive decline, highlighting the need for early intervention. In addition, monitoring intracranial pressure has emerged as a potential biomarker for assessing the impact of vascular aging on the brain, helping to preserve brain integrity and prevent cognitive impairment. In this narrative review, we discuss the pathophysiological mechanisms of vascular aging and their relationship with pulse wave velocity, as well as explore intracranial pressure monitoring as a possible marker for the progression of cerebral vascular aging and its impact on cognitive function.